2015
DOI: 10.1093/eurheartj/ehv583
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and clinical phenotype of hereditary transthyretin amyloid cardiomyopathy in patients with increased left ventricular wall thickness

Abstract: Five per cent of patients diagnosed with hypertrophic cardiomyopathy have mTTR-FAC. Mutated transthyretin genetic screening is warranted in elderly subjects with increased LVWT, particularly, those of African descent with neuropathy, carpal tunnel syndrome, ECG low voltage, or LGE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
110
1
13

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 185 publications
(138 citation statements)
references
References 24 publications
3
110
1
13
Order By: Relevance
“…26 Moreover, the Beta-Blocker Evaluation of Survival Trial study showed a high prevalence of the Val122Ile variant in elderly African Americans with severe HF. In a prospective multicentre study in France, genetic screening for a TTR gene revealed that 5% of 298 consecutive elderly patients (>60 years old) clinically diagnosed with HCM have ATTRv-CA with a predominance of the Val122Ile variant.…”
Section: Implications Of Genetic Diagnosis Of Transthyretin Gene Sequmentioning
confidence: 99%
“…26 Moreover, the Beta-Blocker Evaluation of Survival Trial study showed a high prevalence of the Val122Ile variant in elderly African Americans with severe HF. In a prospective multicentre study in France, genetic screening for a TTR gene revealed that 5% of 298 consecutive elderly patients (>60 years old) clinically diagnosed with HCM have ATTRv-CA with a predominance of the Val122Ile variant.…”
Section: Implications Of Genetic Diagnosis Of Transthyretin Gene Sequmentioning
confidence: 99%
“…Surprisingly, the most common mutation was TTR V122I. 21 The ethnic origin of the V122I-positive subjects is under investigation.…”
Section: Disease Associationsmentioning
confidence: 99%
“…Clinical and imaging findings may be attributed to other causes of left ventricular hypertrophy and delay diagnosis, while more extensive deposition can mimic hypertrophic cardiomyopathy. 34 Atrial arrhythmias are frequent and the risk of left atrial appendage thrombosis is increased. 35,36 …”
Section: Early Diagnostic Cluesmentioning
confidence: 99%